New Array Approaches to Explore Single Cells Genomes - Vanneste, Evelyne; Bittman, Lilach; Van der Aa, Niels; Voet, Thierry; Vermeesch, Joris R. (Frontiers in Genetics, 2012)
Microarray analysis enables the genome wide detection of copy number variations and the investigation of chromosomal instability. Whereas array techniques have been well established for the analysis of unamplified DNA derived from many cells, it has been more challenging to enable the accurate analysis of single cell genomes. In this review, we provide an overview of single cell DNA amplification techniques, the different array approaches and discuss their potential applications to study human embryos.